Electrical Pudendal Nerve Stimulation for Post-Radical Prostatectomy Urinary Incontinence: A Prospective Study - Yueting Chen; Xiaodong Jin; Qian Hong; Fangchao Wu; Shan Chen (American Journal of Men's Health, 2025)
This study compares the clinical efficacy of electrical pudendal nerve stimulation (EPNS) with pelvic floor muscle training (PFMT) in treating post-radical prostatectomy urinary incontinence (PRPUI). A total of 26 patients with PRPUI were divided into a treatment group (14 cases) and a control group (12 cases) based on their choice of therapy. The control group underwent PFMT, while the treatment group received EPNS. The number of pads used, 24-hr pad test and the International Consultation on Incontinence Questionnaire Short Form (ICI-Q-SF) were observed and scored for both groups before treatment and at 8 weeks of treatment, and the clinical efficacy was evaluated. Pelvic floor neuroelectrophysiology indicators of pudendal somatosensory evoked potentials, pudendal skin sympathetic reflex, bulbocavernosus reflex, and needle electromyography were also collected from 11 out of 26 patients. Compared with pretreatment, scores of the number of pads used, 24-hr pad test, ICI-Q-SF, and sum scores in both treatment and control groups decreased significantly after treatment ( p  < .05); the treatment group showed significantly higher differences in the pre- and post-treatment scores of the number of pads used, 24-hr pad test, ICI-Q-SF, and sum scores compared to the control group ( p  < .01). The improvement rate in the treatment group was significantly higher than that of the control group (59.60% vs. 21.98%, p  < .01). Pudendal nerve damage was implicated through pelvic floor neuroelectrophysiology. These findings suggest that EPNS can significantly improve the clinical symptoms of PRPUI (Trial Registration Number: ChiCTR2200055461).